MODERN TECHNOLOGY TO DIAGNOSE EARLY POSTPARTUM HEMORRHAGE IN ISLAND AREAS : A SYSTEMATIC REVIEW - Tiyara Safitri; Respatiningrum Respatiningrum; Fidyah Aminin (International Journal of Social Science, 2022)
Mortality and morbidity due to bleeding occur due to delayed care. On the island, more advanced technology models based on the 4.0 digital development facilities and infrastructures are important to improve the health service quality. This literature review identifies modern technology-based bleeding detection as an effort to detect and diagnose early postpartum hemorrhage on the island. This systematic review study selected the data with the PRISMA protocol method. The researchers took 12 journal article outlets with years of publications from 2011 until 2020. The researchers found 587 articles. However, the most relevant articles with the applied keywords were 12 articles. Various modern technology-based detections for bleeding applied pantograph, gravimetric, bag collector, under-buttock, SAPHE mat, and scoring measurement to efficiently promote early bleeding. These investigated models were more effective than visual estimation with effectiveness percentages of 25-89%. Technology-based detections could early detect and facilitate postpartum hemorrhage and provide immediate care. High technological advancement in the health field facilitates the patients' care, especially in islands that need immediate action. The results of this research are useful to promote further research about modern-technology-based models to detect and diagnose postpartum hemorrhage in islands.